Simulation of Direction of Arrival Using MUSIC Algorithm and Beamforming using Variable Step Size LMS Algorithm - Ahmed, IMustaq; Anirudh Koushik, B.A; Charan Kumar, G.M; Neethu, S (2022 IEEE Microwaves, Antennas, and Propagation Conference (MAPCON), 2022)
In signal processing applications smart antenna arrays are used to locate sources of various signals and for beamforming. Various algorithms have been developed to determine or estimate the Direction Of Arrival (DOA). Direction Of Arrival estimation is utilized in a number of applications, including radar, navigation, communication, etc. Beamforming is a technique used for directive signal transmission and reception. In a smart antenna system antenna arrays adjusts the main lobe towards the desire user and generates null in the direction of interfering users to provide suppression. Objective of this paper is to analyze the performance of Multiple Signal Classification (MUSIC) algorithm a subspace method to estimate DOA and compare with classical Bartlett method of DOA. Beamforming algorithms like LMS and NVSSLMS are studied,analyzed and its performance parameters compared.